Clinical study of factors affecting outcome of tubal recanalization using microsurgical techniques: a retrospective study - G., Rashmi A.; Singh, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In India, many couples complete their families by the age of 25 to 30 years and opt for tubal sterilization as a method of family planning in spite of availability of other spacing methods. Due to unforeseen circumstances, 10 % of them regret their decision and about 1% want to restore their fertility due to various reasons like loss of only child, loss of male child, desire to have more children, loss of children in natural calamities, remarriage and other socioeconomic factors. The objective of the present study was to analyze various factors which are involved in pregnancy rate in tubal recanalization. Methods: 31 women undergoing microsurgical tubal recanalization by mini laparotomy in RRMCH, Bengaluru during a study period of 2 year from 2014 -2016 were followed up for a period of 2 years by telephonic conversation. Results: An overall 67.7 % pregnancy rate was achieved with microsurgery technique. Conclusions: The important factors determining the success of operation were age of the patient, method of previous ligation and the remaining length of tube after recanalization. The microsurgical technique should be available at specialized centres to improve the success of family planning services and also this could be the hope for hopeless.